Langerhans cell histiocytosis presented as bilateral otitis media with effusion, a rare case report - Soheil Motamed; Maryam Amizadeh; Shahriar Dabiri (Babol University of Medical Sciences, 2023)
Background: Langerhans cell histiocytosis (LCH) or histiocytosis X is considered as a rare disease that may have effect on multiple organs. The initial presentation of LCH is varied. The signs and symptoms of otologic histiocytosis can be the same as the acute or chronic infectious ear diseases. Definitive diagnosis of LCH is confirmed by biopsy and immunohistochemically staining of S-100 protein and CD1a antigen. Chemotherapy is the main mode of treatment. Case presentation: In this report, we explained the clinical manifestation, diagnosis and treatment of a case of 15 month-old girl with diagnosed of LCH that initially presented with otitis media with effusion (OME). Conclusion: LCH is a rare disease that presented with variable sign and symptoms and have an effect on multiple organs. LCH should be regarded in cases with recurrent ear infection without response to medical treatments. Moreover, biopsy with IHC is the gold standard of diagnosis and chemotherapy is the main form of treatment.